Estudo dosimétrico de SAF e dose absorvida por atividade injetada de radiofármacos utilizando fantomas computacionais - Carlos Vinícius Gomes Ferreira (2022)
Nuclear medicine (MN) is an area of medicine that uses radiopharmaceuticals for diagnosis, therapy or theranostics. Radiopharmaceuticals are compounds formed by the binding of a drug or molecule with a specific radioactive material used for the treatment of various diseases. The use of radioactive material for MN applications must be performed within a known, robust and well-defined protocol, considering the internal radiation dose to which the patient will be exposed. With the remarkable increase in the use of radionuclides for diagnostic and therapeutic procedures, committees such as Medical Internal Radiation Dose (MIRD) and International Commission on Radiological Protection (ICRP) were created to control and limit the use of radioactive material. Work has been developed over the years by research groups around the world to understand and develop dose estimation protocols, such as the international OpenDose project. This research project has the general objective of calculating and analyzing the various dosimetric parameters (SAF, S-value, absorbed dose and effective dose per injected activity) used in nuclear medicine procedures. The realization took place through modeling and computer simulations using several voxelized phantoms and the Monte Carlo code EGSnrc. Guidelines for producing SAF values were defined by OpenDose and the results are published at the website of MCMEG. The S-values, absorbed dose and effective dose per injected activity were calculated for the 18 F-FDG and 99m Tc-DMSA administered in pediatric phantoms. In addition, the biodistribution for 18 F-FDG proposed by ICRP 128 and other authors for pediatric patients was studied. New radiopharmaceuticals, such as 43/44/44m Sc- and 68 Ga-DOTATATO, used for theranostic area, and unprecedented dosimetry data were obtained for ICRP adult reference computational phantoms 110. From the SAF results calculated for the source organs (r S ) brain and thyroid, the mean of the relative errors between the simulated SAF and SAFerr values was less than 15% for the brain and less than 8% for the thyroid. The results for the administration of the radiopharmaceuticals 18 F-FDG and 99m Tc-DMSA in pediatric phantoms obtained for absorbed dose per injected activity (AD/IA) showed averages ∆ between organs , considered major from their biodistributions, less than 85%. From the biokinetic data of the radiopharmaceuticals 43/44/44m Sc- and 68 Ga-DOTATATO, the average ∆% of the AD/IA results of the AF phantom ranged between –4% and 3% and for the AM phantom, between -13% and 2%, considering the comparison between EGSnrc/MCNP6.1 and EGSnrc/OLINDA. In general, all the results obtained are in good agreement with the expected.